CONTRIBUTION OF PALM SUGAR BUSINESS TO FAMILY ACCEPTANCE IN SELUPU REJANG SUBDISTRICT OF REJANG LEBONG REGENCY - Mira Yanuarti; Meza Yolanda (Jurnal AGRIBIS, 2021)
This study aims to calculate the large acceptance of palm sugar business during the Covid-19 Pandemic. Calculating the contribution of palm sugar business income to the acceptance of craftsmen's families during the Covid-19 pandemic.the research was conducted using purposive sampling method as a consideration material, namely in 2020 the amount of palm sugar production in Selupu Rejang Subdistrict reached 5,441.68 Tons with a palm plant area of 2,280 ha.The analysis tools used are income analysis of palm sugar processing business and analysis of business income contribution.The results showed that during the Covid-19 pandemic the average acceptance of palm sugar business in Selupu Rejang subdistrict was an average of Rp.2,019,501/month average production cost was Rp.1,020,602.50/mo. So it is known that the average income of palm sugar craftsmen is Rp.982.357.50/mo. The contribution of palm sugar income during the Covid-19 pandemic is 5.54% so it can be concluded that the palm cave processing business is a side business and the largest contribution of income obtained from other businesses.